2006
DOI: 10.1002/jat.1134
|View full text |Cite
|
Sign up to set email alerts
|

Preferential expression of matrix metalloproteinase-9 in mouse skin after sulfur mustard exposure

Abstract: Matrix metalloproteinases (MMPs), a class of enzymes responsible for the degradation of extracellular matrix proteins, play important roles in inflammatory and immune responses. In skin, MMP-2 (gelatinase A) and MMP-9 (gelatinase B) are normally inactive but can be expressed during tissue injury. Both degrade collagen IV and other critical components of the basement membrane zone that separates the epidermis from the dermis. The expression of MMP-2 and -9 was studied in sulfur mustard (SM)-exposed ear skin fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
59
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 28 publications
10
59
1
Order By: Relevance
“…Interestingly, our results may thus suggest that mast cells would play an important role in SMinduced microvesications, as mast cell degranulation and increase in MMP9 mRNA occur before the appearance of microvesications which are associated with the presence of neutrophils in fluid blisters. This hypothesis is concordant with previous reports showing a great increase of tryptase activity (Powers et al, 2000) and the preferential expression of MMP9 in skin (Shakarjian et al, 2006) after SM exposure in the mouse ear vesicant model.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, our results may thus suggest that mast cells would play an important role in SMinduced microvesications, as mast cell degranulation and increase in MMP9 mRNA occur before the appearance of microvesications which are associated with the presence of neutrophils in fluid blisters. This hypothesis is concordant with previous reports showing a great increase of tryptase activity (Powers et al, 2000) and the preferential expression of MMP9 in skin (Shakarjian et al, 2006) after SM exposure in the mouse ear vesicant model.…”
Section: Discussionsupporting
confidence: 93%
“…Increases in MMP are of particular interest because of their ability to cleave basement membrane components and thus disrupt dermal/epidermal junction. This is clearly illustrated by animal studies demonstrating an increase expression of mRNA and/ or protein levels for MMP-9 in SM-exposed skin Dachir et al, 2010;Sabourin et al, 2002;Shakarjian et al, 2006;Vallet et al, 2012).…”
Section: Introductionmentioning
confidence: 84%
“…One hypothesis for vesicant action is the activation of an endogenous protease by SM [7][8][9][10] and an endogenous inhibitor of this protease has been identified [11,12]. Other investigators have analyzed the effects of SM on basal cell adhesion complex molecules [13][14][15][16][17], hypothesizing alkylation of basal cell adhesion complex molecules results in failure of the complex [16,18], leading to blister formation, similar to inherited skin blistering diseases [19].…”
Section: Introductionmentioning
confidence: 99%
“…Some in vitro and animal model studies have reported the association of acute SM complications with changes in MMP expression [29][30][31]. In a study on mice ear skin 7 days after exposure to SM, relative levels of MMP-9 mRNA and protein were increased 27-and 9-folds respectively compared to the control group [31].…”
Section: Discussionmentioning
confidence: 96%